2012
DOI: 10.3109/14992027.2012.705903
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled comparison of NAL and DSL prescriptions for young children: Hearing-aid characteristics and performance outcomes at three years of age

Abstract: Objective To determine the influence of choice of prescription and other child-, family- and intervention-related factors on speech, language, and functional performance of hearing-impaired children by three years of age. Design and study sample A randomized controlled design was implemented as part of a population-based, longitudinal study on outcomes of children with hearing impairment (LOCHI) in Australia. Two hundred and eighteen children were randomly assigned to either the NAL or the DSL prescription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
2
20
1
Order By: Relevance
“…This value exceeded the 5 dB criterion set forth in previous adult studies of proximity related to prescriptive target (Byrne & Cotton, 1988; Cox & Alexander, 1990; Baumfield & Dillon, 2001; Polonenko et al 2010). The current cohort of hearing-aid fittings also deviated from prescriptive target to a greater degree than published reports evaluating the relationship between prescriptive approaches and developmental outcomes in children (Ching et al 2012). For children with mild to severe hearing loss, fitting the hearing aid within 5 dB of prescriptive targets represents a reasonable and achievable standard if appropriate verification methods are used.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This value exceeded the 5 dB criterion set forth in previous adult studies of proximity related to prescriptive target (Byrne & Cotton, 1988; Cox & Alexander, 1990; Baumfield & Dillon, 2001; Polonenko et al 2010). The current cohort of hearing-aid fittings also deviated from prescriptive target to a greater degree than published reports evaluating the relationship between prescriptive approaches and developmental outcomes in children (Ching et al 2012). For children with mild to severe hearing loss, fitting the hearing aid within 5 dB of prescriptive targets represents a reasonable and achievable standard if appropriate verification methods are used.…”
Section: Discussionmentioning
confidence: 56%
“…The vast majority of service providers reported using the DSL prescriptive method (98%; 123/125), while the remaining two service providers reported using NAL-NL1. Recent studies suggested that although there are differences between DSL v. 4 and NAL-NL1 in both gain and output, speech recognition and audibility outcomes are similar between the two prescriptions(Scollie et al, 2010; Ching et al, 2010; Ching et al 2012). Comparisons are further complicated by the fact that updated versions of each algorithm (DSL v.5 and NAL-NL2) have been developed and are used clinically by pediatric audiologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For children with ANSD, the audiogram for fitting was estimated on the basis of the minimum response levels obtained during behavioral observation audiometry (BOA) assessments, together with measurements of cortical auditory evoked potentials (CAEP) using speech-sound stimuli developed in a previous study (Golding et al, 2009), as well as parental reports (Ching & Hill, 2007). Children who enrolled in the study prior to initial amplification were randomly assigned to being fitted with either the National Acoustic Laboratories prescription for non-linear hearing aids, version 1 (NAL), or the desired sensation level, version 4.1 (DSL) prescription (Ching et al, 2013a). Those who enrolled after initial fitting were fitted with hearing aids using the NAL prescription.…”
Section: Methodsmentioning
confidence: 99%
“…Two prescriptive methods have been widely validated for children who wear HAs: the National Acoustics Laboratories Nonlinear Formula, Version 2 (NAL-NL2; Keidser et al, 2011) and the Desired Sensation Level multistage input/output, Version 5 (DSL m i/o; Scollie et al, 2005). Both formulae have been validated for use with children, including a randomized controlled trial where equivocal results were observed among children fitted with each formula (Ching et al, 2013a). Hearing aid fittings that more closely approximate prescriptive targets have been shown to provide more consistent speech audibility across a range of degrees of hearing loss than fittings with significant deviations (McCreery et al, 2013).…”
Section: Introductionmentioning
confidence: 99%